Les Quinquagénaires au Travail selon les Classes Sociales - Riverin-Simard, Danielle (Canadian Journal for the Study of Adult Education, 1988)
Résumé Cet article décrit la vie professionnelle de l'adulte quinquagénaire, selon son appartenance sociale. Pour ce faire, on a interviewé 101 sujets de 53-57 ans de la région administrative 03 du Québec. Les sujets ont été choisis au hasard et répartis a priori selon les variables suivantes: classe socio-économique, sexe et secteur de travail. Les résultats globaux révèlent que l'adulte de 53-57 ans est à la recherche d'une sortie prometteuse du marché du travail au sein de laquelle il tend à démontrer qu'il a rempli d'une façon exemplaire les rôles respectifs de supporter (classe moyenne), de serviteur (classe défavorisée) ou de leader (classe aisée). Les propos reliés à l'éducation des adultes ne sont présents que chez les sujets-exceptions. This article describes the working life of adults in their fifties, according to the social class to which they belong. Data were obtained from individual interviews with 101 research subjects whose ages ranged from 53 to 57 years. They were selected randomly from the 03 Administrative Region of Quebec in such a way that the sexes were equally represented, as were the three socio-economic classes (upper, middle and lower), and the three sectors of the economy (private, public and quasi-public). The overall findings reveal that adults in this age range are looking for a promising departure from the labour market. In describing how they were fulfilling their roles in exemplary fashion, the upper class person spoke of his or her leadership role, the middle class person of a supporting role, and the lower class person of the servant role. Very few of the research subjects mentioned adult education.